Performance of Anticorrosive Paint Systems for Carbon Steel in the Antarctic Marine Environment - Rosa Vera; Margarita Bagnara; Rodrigo Henríquez; Lisa Muñoz; Paula Rojas; Andrés Díaz-Gómez (Materials, 2023)
This study evaluated the behavior of three paint systems exposed to the Antarctic marine environment for 45 months compared to a control of uncoated carbon steel with a determined corrosion rate. At the study site, all environmental conditions, solar radiation, and the concentration of environmental pollutants (Cl− and SO2) were evaluated. The paint systems differed in terms of the primer and top coat. Coated samples were studied before and after exposure. They were evaluated visually and using SEM to determine adhesion, abrasion, and contact angle; using the Evans X-Cut Tape Test; using ATR-FTIR spectroscopy to analyze the state of aging of the top layer; and using electrochemical impedance spectroscopy (EIS) for coat protection characterization. The corrosion rate obtained for steel was 85.64 µm year−1, which aligned with a C5 environmental corrosivity category. In general, the evaluation in the period studied showed the paint systems had good adhesion and resistance to delamination, without the presence of surface rust, and exhibited some loss of brightness, an increase in the abrasion index, and a decrease in the percentage of reflectance due to aging. EIS showed good protection capability of the three coating schemes. In general, this type of paint system has not previously been evaluated in an extreme environment after 45 months of exposure to the environment. The results showed that the best behavior was found for the system whose top layer was acrylic–aliphatic polyurethane.